Analisis Kesalahan Penggunaan EYD Pada Modul Ajar Tema 7 Kelas IV SD (Sekolah Tinggi Agama Buddha Nalanda, 2023)
This study aims to analyze the form of errors in the use of EjYD in the theme 7 class 6 teaching module. The data in this study are errors in the use of EYD in the theme 7 class 6 teaching module. The data source in this research is the theme 7 class 6 teaching module. The results of the study show that found as many as 10 punctuation errors, 4 word writing errors, and 4 letter writing errors. Based on the results of the study, it was shown that the most errors were in the writing of punctuation marks, this could have happened because the author of the teaching module had not mastered the EYD technique, but it could also be due to a lack of accuracy when writing this module.